Relapse after treatment of pediatric hodgkin lymphoma: Outcome and role of surveillance after end of therapy. Issue 9 (15th May 2013) - Friedmann, Alison M.; Wolfson, Julie A.; Hudson, Melissa M.; Weinstein, Howard J.; Link, Michael P.; Billett, Amy; Larsen, Eric C.; Yock, Torunn; Donaldson, Sarah S.; Marcus, Karen; Krasin, Matthew J.; Howard, Scott C.; et al.
Abstract Background The outcome of treatment for pediatric Hodgkin lymphoma (HL) is excellent using chemotherapy and radiation. However, a minority of patients will relapse after treatment, but additional therapy achieves durable second remission in many cases. The optimal surveillance strategy after modern therapy for HL has not been well defined. Procedures We reviewed the outcomes of pediatric patients with HL treated between 1990 and 2006 to determine the primary event that led to the detection of relapse. We determined the probability of relapse detection by routine follow‐up procedures, including history, physical examination, laboratory tests, and imaging, and determined the impact of each of these screening methods on the likelihood of survival after relapse. Results Relapse occurred in 64 of 402 evaluable patients (15.9%) at a median of 1.7 years from the time of diagnosis. The majority of relapses (60%) were diagnosed at a routine visit, and patient complaint was the most common initial finding that led to a diagnosis of relapse (47% of relapses). An abnormal finding on physical examination was the primary event in another 17% of relapses, and imaging abnormalities led to the diagnosis in the remaining 36%. Laboratory abnormalities were never the primary finding. The method of detection of relapse and timing (whether detected at a routine visit or an extra visit) did not impact survival. Conclusions In pediatric HL, most relapses are identified through history and physical examination. Frequent imaging of asymptomatic patients does not appear to impact survival and is probably not warranted. Pediatr Blood Cancer 2013;160:1458–1463. © 2013 Wiley Periodicals, Inc.